Daya Terima Flakes Tepung Bekatul dan Tepung Jagung Sebagai Makanan Selingan Tinggi Serat - Dian Muliani; Sartono Sartono; Yulianto Yulianto (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Flakes are a form of ready-to-eat cereal product. In general, flakes are made from wheat flour or from starch such as tapioca flour. However, at this time innovation has been developed in the processing of flakes. Flakes with the addition of bran flour and corn flour which are rich in fiber are also very suitable for consumption as a diet food or an alternative snack for overweight teenagers. Objective: To determine the acceptability of bran flour and corn flour flakes as high fiber snacks. Method: Experimental method with non-factorial Completely Randomized Design (CRD). Using the Organoleptic Test with 25 panelists. Determination of nutritional value and fiber using proximate analysis and fiber analysis. Results: The selected flakes formulation of bran flour and corn flour was F2 (30 grams of rice bran flour and 70 grams of corn flour) with an energy content of 403.61 Kcal, 8.5% protein, 6.91% fat, 76.84% carbohydrates. , 3.79% moisture content, 3.94% ash content, and 7.19% fiber in 100 g of flakes. Based on the Friedman test, there was no significant effect between the acceptance of bran flakes and corn flour on color (p = 0.251), taste (p = 0.006), aroma (p = 0.821), and texture (p = 0.553). Conclusion: Flakes with the addition of rice bran flour and corn flour can be used as an alternative snack that is high in fiber.